Hydrocarbons in the bottom sediments of the Northern Dvina estuary. - Nemirovskaya, Inna A (PANGAEA, 2007)
The results of studying hydrocarbons during the flood in May 2005 are discussed. The concentration of aliphatic and polycyclic aromatic hydrocarbons are shown to match their concentrations in water areas with steady input of pollutants. Weathered oil and pyrogenic compounds dominated in their composition. The geochemical barrier the Northern Dvina River-Dvina Gulf is shown to become a filter during floods and prevents pollutants from penetrating into the White Sea.
Hydrocarbons in bottom sediments during a seasonal flood 2005 in the Dvina River estuary
Keywords: Archive of Ocean Data; ARCOD